Fluorocarbon Vapors Slow Down Coalescence in Foams. Issue 20 (19th September 2021) - Steck, Katja; Hamann, Martin; Andrieux, Sébastien; Muller, Pierre; Kékicheff, Patrick; Stubenrauch, Cosima; Drenckhan, Wiebke
Abstract: Controlling the stability of liquid foams is of the utmost importance for a wide range of applications. For decades, fluorocarbon vapors have been added to the gas phase of foams to ensure long‐term stability against bubble coarsening. However, it is shown here for the first time that they also have an unexpected and pronounced effect on bubble coalescence. This effect is quantified in detail for foams stabilized by the nonionic surfactant hexaethylene glycol monododecyl ether (C12 E6 ) at controlled fluorocarbon (perfluorohexane (C6 F14 )) concentrations, but it is observed for all investigated surfactants. Measuring surface tensions of the foaming solution with increasing fluorocarbon concentration, a synergy between the fluorocarbon and the surfactant is found which can be explained by a) the formation of mixed layers of both species at the gas/water interface at low fluorocarbon concentrations and b) the formation of a macroscopic fluorocarbon film if the gas phase is saturated with fluorocarbon vapor. The precise mechanism responsible for reducing coalescence, that is, film rupture, remains to be elucidated. Abstract : Tuning the stability of liquid foams remains a major challenge for the optimization of applications. The use of co‐adsorbates from the gas phase is a new possibility to control this stability. It is shown that fluorocarbon (FC) vapors not only prevent gas exchange between bubbles, as widely known, but also efficiently increase the stability of the foam films against rupture.